Implementation of Smarat Vilage In Sendang Agung Village Mobile Web Based As An Effort to Support Law Number 14 of 2008 Concerning Public Information Disclosure - Muslihudin, Muhammad; Arifin, Febrianto; Mardeli, Iis (JLASA (Journal of Law and State Administration), 2024)
This study aims to implement the Smart Village concept in Sendang Agung Village through the development of a mobile web-based information system to support public information disclosure as mandated by Law Number 14 of 2008. The lack of public access to transparent and accountable village information highlights the need for a digital system that is easily accessible to all community members. The research method used is Research and Development (R&D) with a waterfall model approach in software development. The system provides various village information features such as event schedules, financial reports, social assistance data, and online administrative services accessible via mobile devices. Testing results indicate that the application improves the efficiency of information dissemination and received positive feedback from village officials and residents. This implementation is expected to position Sendang Agung Village as a model of a digital village that promotes openness and active public participation.